The Effect Of Feeding Gliricidia Sepium Leaf in The Dry Season on Ettawah Cross Bred Goat Milk Production and Quality at Households of Tumpang Regency in Malang Districts - Hidayati, Asmah (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This research was conducted during dry season in Tumpang Regency of Malang Districts. Theaim of this research was to study Gliricidia sepium (G. sepium) leaf in ration and its effect on milkproduction and quality of Ettawah Crossed Bred Goats (ECDG). Twenty five households weresurveyed and divided into 5 groups based on the level of G. sepium used in ration. The 5 groupswere Gs-0 (no G. sepium in the ration); Gs-1 (G.sepium 1-20% of the ration), Gs-2 (G. sepium of 2130%),Gs-3(G.sepiumof31-40%),andGs-4(G.sepiumof41-50%). Every week samples of milk were sampled for fat quality assessed by the Gerber method in a laboratory. Milk production data wasconverted to ECM values (Hemme, 2010). Dry matter (DM) of the ration was measured in proximateanalyses (AOAC, 1990). The botany composition measuring G. sepium percentage in ration (% DM)were 0 % (Gs-0) 15,62% (Gs-1) 24,94% (Gs-2); 36,94% (Gs-3) and 43,24% (Gs-4). The Crops wastepercentage of DM was 30,63 % (Gs-0) 19,84% (Gs-1) 6,05% (Gs-2); 6,77% (Gs-3) and 9,87% (Gs4).There were significant differences (p<0.01) between the 5 G sepium rations. The ECM, fat andcrude protein content in milk was 1,332; 6,63 and 3,42 (Gs-0) 1,314; 6,58 and 3,27 (Gs-1) 1,322; 6,60and 3,33 (Gs-2); 1,333; 6,6 and 3,37 (Gs-3) and 1,323; 6,8 and 3,2 (Gs-4) respectively. A level of G.sepium leaf up to 40% in ration gradually increases the crude protein and fat content in ECDG milk.Therefore G.sepium leaf of up to 40% DM could increase the quality of Ettawah Crossed Bred DairyGoat (ECDG) milk with regards to protein and fat content.Key Words: G Sepium, ECDG Milk Production and Quality